Mechanochemical synthesis of NbC–NbB2 nanocomposite from the Mg/B2O3/Nb/C powder mixtures. Issue 4 (May 2015) - Torabi, Omid; Naghibi, Sanaz; Golabgir, Mohammad Hossein; Tajizadegan, Hamid; Jamshidi, Amin
Abstract: An experimental study was conducted on the preparation and characterization of nanocrystalline niobium boride and carbide composite (NbB2 –NbC) in the Mg–B2 O3 –Nb–C system via mechanochemical method. The thermodynamic appraisal indicated that the reduction and synthesis reactions were highly exothermic and should be self-sustaining. According to the differential thermal analysis (DTA) results, a pre-milling treatment of powder mixture up to 2 h not only reduced the reaction temperature, but also induced a different reaction path. In addition, the amount of Mg3 (BO3 )2, as a major by-product of the thermal synthesis, was significantly decreased by applying adequate mechanical activation. The phase analysis revealed that the NbB2 phase was achieved after 3 h high energy ball milling in self-stunning mode; meanwhile, the formation of NbC was progressively completed after a longer period of milling up to 7 h. According to the morphological evolutions, the range of particle size was within 100 nm.